Análisis epistemológico de la educación ecuatoriana: Aportes desde la teoría crítica - Gaona Merino, Edwin Saul (2014)
The analysis of the history of education in Latin America since the early twentieth century allows us to understand the causes of our underdevelopment, one of its roots with retrograde visions imposed on us over the neoliberal era. From quit attempts until dictatorial visions and privatization, our public education has resisted these attacks, taking the ruling class against him. The contribution of Paulo Freire in the 80s marks a milestone in the theoretical and practical transformation from a centered pedagogy and subject to the Latin American context. The new provisions of the institutions of social control and political education should help the pedagogical models allow Ecuadorian students to appropriate science for the transformation of society. Social theory criticizes philosophers of Frankfurt and new contributions from Latin America provide us with the necessary arguments to build science from and to Latin America in order to solve our problems.